Developing Rural School Leaders Through Leadership Coaching: A Transformative Approach. Issue 4 (1st October 2020) - Klar, Hans W.; Huggins, Kristin Shawn; Andreoli, Parker M.; Buskey, Frederick C.
ABSTRACT: In this article, we report the findings of a study of a three-year, research-practice partnership designed to enhance the leadership capabilities of school leaders in 12 predominantly rural, high-poverty school districts in the southeastern United States. The partnership provided cross-district, job-embedded leadership development to ten school leaders through leadership coaching in a leadership learning community (LLC). Utilizing transformative learning theory, we illustrate how the leaders' participation in the LLC increased their leadership capabilities through a combination of personalized learning, a focused improvement process, facilitation and coaching, and collaboration with other leaders. We conclude with implications for research and practice.